The relationship between CO2 emissions, energy consumption and economic growth in Italy. Issue 9 (20th October 2016) - Magazzino, Cosimo
Abstract : This study examines the relationship between CO2 emissions, energy consumption and economic growth in Italy over the period 1970–2006. Results of unit root tests show that all variables are non-stationary in their level form, but stationary in first differences form. The causal relationship between variables is examined using causality test in a vector autoregressive framework. Our empirical results show that CO2 emissions, energy consumption and economic growth are not cointegrated. Moreover, the Toda and Yamamoto Granger non-causality test shows a bidirectional causality between CO2 emissions and economic growth, as well as between CO2 emissions and energy consumption. Forecast error variance decompositions evidence that the errors in real per capita GDP are mainly due to uncertainty in GDP itself, while the errors in predicting the energy consumption and the CO2 emissions are sensitive to disturbances in the other two equations.